2011
DOI: 10.1038/nchembio.717
|View full text |Cite
|
Sign up to set email alerts
|

FERM domain interaction with myosin negatively regulates FAK in cardiomyocyte hypertrophy

Abstract: Focal adhesion kinase (FAK) regulates cellular processes that affect several aspects of development and disease. The FAK N-terminal FERM (4.1 protein-ezrin-radixin-moesin homology) domain, a compact clover-leaf structure, binds partner proteins and mediates intramolecular regulatory interactions. Combined chemical cross-linking coupled to MS, small-angle X-ray scattering, computational docking and mutational analyses showed that the FAK FERM domain has a molecular cleft (~998 Å(2)) that interacts with sarcomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
0
18
0
3
Order By: Relevance
“…A complete understanding of how an interplay with aB-crystallin results in regulation of FAK function requires knowledge of structural features of the aB-crystallin:FAK complex. In this study, we used protein chemical crosslinking combined with mass spectrometry and mutational analyses 26,27 to show that a surface-exposed patch sited between a1 and a4 helices of the FAK FAT domain binds to the b4-b8 hydrophobic groove of ACD. The hydrophobic nature of the FAK FAT a1-a4 ARTICLE patch has been reported to favour its sequestration within intermolecular interfaces of FAK protein partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete understanding of how an interplay with aB-crystallin results in regulation of FAK function requires knowledge of structural features of the aB-crystallin:FAK complex. In this study, we used protein chemical crosslinking combined with mass spectrometry and mutational analyses 26,27 to show that a surface-exposed patch sited between a1 and a4 helices of the FAK FAT domain binds to the b4-b8 hydrophobic groove of ACD. The hydrophobic nature of the FAK FAT a1-a4 ARTICLE patch has been reported to favour its sequestration within intermolecular interfaces of FAK protein partners.…”
Section: Discussionmentioning
confidence: 99%
“…To gather information on the structural features of the FAKcTERM-CryAB complex, we used crosslinking in combination with mass spectrometry (CXMS) analysis and computational modelling 26,27 . Given the size and high flexibility of the multidomain full-length FAK, we decided to use the truncated FAK-cTERM in the structural and computational studies.…”
Section: Structural Basis Of the Fak-cterm-ab-crystallin Interactionmentioning
confidence: 99%
“…It has been recently reported that the interaction of FERM with myosin negatively regulates FAK activity by promoting the autoinhibited FAK conformation (43). This recent study provided strong evidence of direct interaction between myosin heavy chain Integrin α5β1 can be fully activated in the tensioned state where both RGD peptide (yellow circle) and synergy site (red circle) bind to α5 and β1 subunits, respectively.…”
Section: Distinct Biophysical Mechanism Of Fak Mechanoactivation Detementioning
confidence: 83%
“…The key residues of FERM F2 domain for myosin binding, E158/D161/Q162 (EDQ) (43), are positioned proximal to the FERM F2 basic patch KAKTLRK (SI Appendix, Fig. S14A).…”
Section: Distinct Biophysical Mechanism Of Fak Mechanoactivation Detementioning
confidence: 99%
See 1 more Smart Citation